The Establishment of Islamic Dwelling Principles for the Malaysian Communities - Ismail, WNW; Arabi, F; Husini, EM; Zolkifly, FNS; Darus, ZM; Jaafar, NHA; Manaf, AA (Amer Scientific Publishers, 2024)
Indexed by WOS/ Scopus